Perencanaan Predictive Dan Preventive Maintenance Pada Pompa SWLP (Sea Water Lift Pump) Dengan Menggunakan Metode RCM (Reliability Centered Maintenance) Di Saka Indonesia Pangkah Limited - Huda, Samsul; Tripariyanto, Afiff Yudha; Komari, Ana (Universitas Kadiri, 2021)
One of the equipment used in the oil and gas industry is the Service Water Lift Pump (SWLP). The pump is used for operations at Saka Indonesia Pangkah Ltd. The pump has components that are interrelated, if there are components that have a problem it will cause undisturbed activity. This study aims to look at critical components based on RPN, replacement interval time and recommendations on treatment measures. The research limitation is using the RCM method based on the highest RPN value on 2 critical components of FMEA with Downtime data from January 2018 to April 2020. Then use RCA as LTA Aster. Data analysis techniques for selecting the hierarchy of functions and SWLP components, data retrieval, downtime calculations, creating system boundaries, system descriptions and making functional block diagrams. Followed by determining the function, malfunction, FMEA calculation to see the highest RPN value on 2 critical components. Then the normal distribution model is calculated to produce the MTTR and MTTF values. Making Fishbone Diagram to identify critical component problems, to recommend corrective actions. This study resulted in a discussion and reports that critical components include: Mechanical Seal Cartridges with an RPN value of 54, with an RPN value of 48. The critical components for the application of RCM are Mechanical Seal Cartridges with a duration of use for 3.62 months and a repair time of 1400 hours and Bearings. with an interval of 3.27 months and a repair time of 705 hours. Repair recommendations based on the Fishbone Diagram are inspected to avoid damage, damage, when component repairs and replacements are carried out, provide motivation to maintenance personnel, use of the best metal materials. Understanding RCM is carried out continuously and evaluates each RCM activity.Â Peralatan yang digunakan pada industri migas salah satunya adalah Service Water Lift Pump (SWLP). Pompa tersebut digunakan untuk kegiatan operasi di Saka Indonesia Pangkah Ltd. Pompa tersebut memiliki komponen yang saling berkaitan, jika ada komponen yang bermasalah akan menyebabkan kegiatan operasi akan terganggu. Penelitian ini bertujuan untuk mengetahui komponen kritis berdasarkan RPN, waktu interval penggantian dan rekomendasi pada tindakan perawatan. Batasan penelitian menggunakan metode RCM berdasarkan nilai RPN tertinggi pada 2 komponen kritis dari FMEA dengan data down-time sejak Januari 2018 sampai April 2020. Kemudian menggunakan RCA sebagai pengganti LTA. Teknik analisis data pemilihan hierarki fungsi dan komponen SWLP, pengambilan data, perhitungan Downtime, membuat batasan sistem, deskripsi sistem dan pembuatan functional block diagram. Penelitian ini menghasilkan pembahasan dan kesimpulan bahwa komponen kritis antara lain : Mechanical Seal Catridge dengan nilai RPN sebesar 54, bearing dengan nilai RPN sebesar 48. Komponen kritis berdasarkan penerapan RCM adalah Mechanical Seal Catridge dengan durasi penggunaan selama 3,62 bulan dan waktu perbaikan 1400 jam dan Bearing dengan interval waktu 3,27 bulan dan waktu perbaikan 705 jam. Rekomendasi perbaikan berdasarkan Fishbone Diagram dilakukan inspeksi untuk menghindari kerusakan, mengetahui kapan perbaikan dan penggantian komponen dilakukan, memberikan motivasi kepada petugas maintenance, penggunaan bahan logam terbaik. Pemahaman RCM dilakukan secara berkelanjutan dan evaluasi setiap aktivitas RCM.